Curcumin reverses hepatic epithelial mesenchymal transition induced by trichloroethylene by inhibiting IL-6R/STAT3. (13th October 2021) - Cao, Weiya; Zhang, Yinci; Li, Amin; Yu, Pan; Song, Li; Liang, Jiaojiao; Cao, Niandie; Gao, Jiafeng; Xu, Ruyue; Ma, Yongfang; Tang, Xiaolong
Abstract: Objective: Epithelial mesenchymal transition (EMT) and inflammation have been identified as carcinogenic agents. This study aims to investigate whether inhibition of trichloroethylene (TCE) associated hepatocellular carcinoma (HCC) by curcumin is associated with inflammation and EMT. Methods: In the current study, TCE sub-chronic cell model was induced in vitro, and the effects of TCE on cell proliferation, migration, invasion, and expression of functional proteins were verified by Western blot, MTT, clone formation, wound healing, Transwell. The detoxification effect of curcumin on TCE was explored by a mouse tumor-bearing experiment. Results: TCE induces hepatocyte migration, colony formation, and EMT in vitro . In vivo studies have shown that curcumin significantly reduces the mortality of mice and control the occurrence and size of liver tumors by inhibiting the IL-6/STAT3 signaling pathway. In vitro, curcumin inhibits the proliferation of HepG2 cells as determined by MTT assay. In addition, curcumin significantly inhibited the protein expression of IL-6R, STAT3, snail, survivin, and cyclin D1 in THLE-2 and HepG2 cells induced by IL-6. Conclusion: Curcumin has anti-inflammatory and anti-proliferative effects, and inhibits the development of HCC induced by TCE by reversing IL-6/STAT3 mediated EMT.